A study on ultrasonic welding of thermoplastics with significant differences in physical properties under different process parameters. (December 2022) - Fu, Xie; Yuan, Xiaoya; Li, Guowei; Wu, Yutong; Tong, Hui; Kang, Shuai; Luo, Jinling; Pan, Ziwei; Lu, Wenqiang
Abstract: Thermoplastics such as polypropylene (PP) and polyamide6 (PA6) with large different physical properties are difficult to welding. The novel ultrasonic welding device introducing the interlayer solder sheet (ISS) and interfacial compatibilization can realize the fusion bonding between PP and PA6. So it is necessary to discuss the influence factors on various process parameters for the mechanical welding performance of these materials. The better weld strength and morphology are related to weld time, weld load, and ISS components. When the process parameters vary in these ranges: welding time: 4–6 s, welding load: 5–7 N, PP-g-MAH contents: 30–70 %, the welding strength shows the better value, while the fracture surface and microstructure of welding interfaces show a perfect welding area with a much more smooth and defect-free uniform microstructure. The ISS with PP-g-MAH contents lower than 50 % has better plasticity, promoting the molecular chain inter-diffusion at the interface, which is beneficial to ultrasonic energy converting to the viscoelastic heat of the material. In addition, too short a weld time (≤2 s) or load (0–2 N) result in lower weld strength with a small welding area for lower interfacial temperature, while too long a weld time (8 s) leads to defective structures at the weld interface, such as bubbles, holes, etc. Graphical Abstract: ga1 Highlights: Based on a novel ultrasonic welding device, an interlayer solder sheet realized weldability for PP and PA6. The better weld strength and morphology were related to weld time (4 6 S), weld load(5 7 N), and ISS components (30 50%). Enough weld load (5 7 N) promoted energy transformation. Proper weld time (4 6 S) ensured the fusion bonding window.